Spring Security LDAP integration and SAML extension - Mishra, Ankit (Packt Publishing, 2017)
"Spring Security is a Java/Java EE framework that provides authentication, authorization and other security features for enterprise applications. Starting with introduction to LDAP, we will develop a Spring Security application integrated with Active Directory LightWeight DS and Apache DS. Later, we will be introduced to SAML and its working, before proceeding to integrate with Spring Security. Here we will also look at the xml and Java configurations combined in one application. Furthermore, we will look at JaaS integration with Spring Security, Oauth2 basics and its working. The integration with Spring Security to create Resource and authorization servers will be explained later on in the final section of the course. Spring Security test-cases along with compatibility to MockMVC is explained at the end summarizing the entire course."--Resource description page